A new genus and new species of a semi-terrestrial freshwater crab from montane tropical rainforests in Java, Indonesia (Decapoda: Brachyura: Gecarcinucidae). Issue 3 (13th March 2018) - Ng, Peter K L; Wowor, Daisy
Abstract: A new genus and new species of highland gecarcinucid crab, Occulthusa halimun, is described from Mount Halimun Salak National Park, West Java, Indonesia. The species can be distinguished from the allied Terrathelphusa kuhlii (De Man, 1883 ) from West Java by a subquadrate carapace that is not prominently inflated, the entire anterolateral margins and subparallel posterolateral margins of the carapace, prominent epigastric and postorbital cristae composed of strong striae, a frontal median triangle that is almost complete, with the dorsal ridge wide and distinct, and a distinctive male first gonopod with a stout subterminal segment and short and strongly bent terminal segment.